PENGARUH KEMATANGAN GURU, LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU PADA MADRASAH ALIYAH NEGERI KABUPATEN BATU BARA - Syahri Mauliddin; Khairunnisya .; Muhammad Sya’i; M. Syafi’i; Ayu Roza Fiitri (Universitas Islam Sumatera Utara, 2020)
Problem of this study is how influence of teacher’s maturity on teacher’s performance. How influence of job environment on teacher’s performance. How influence of head leadership of madrasah on teacher’s performance. How influence teacher’s maturity, job environment and head leadership of madrasah on teacher’s performance. The purpose of this study to determine and analyze the effect of teacher’s maturity on teacher’s performance. Determine and analyze the effect of job environment on teacher’s performance. Determine and analyze the effect of head leadership of madrasah on teacher’s performance. Determine and analyze the effect of teacher’s maturity, job environment and head leadership of madrasah on teacher’s performance. Sample in the study is 52 teacher’s . Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate teacher’s maturity variable has a positive and significant effect on teacher’s performance. Teacher’s job environment variable has a positive and significant effect on teacher’s performance. Head leadership of madrasah variable has a positive and significant effect on teacher’s performance. The teacher’s maturity, job environment and head leadership of madrasah variable has a positive and significant effect on teacher’s performance.